2020
DOI: 10.1002/jbmr.4481
|View full text |Cite
|
Sign up to set email alerts
|

Introduction of a Cys360Tyr Mutation in ANO5 Creates a Mouse Model for Gnathodiaphyseal Dysplasia

Abstract: Gnathodiaphyseal dysplasia (GDD) is a rare autosomal dominant genetic disease characterized by the osteosclerosis of tubular bones and the formation of cemento-osseous lesions in mandibles. Although genetic mutations for GDD have been identified in the ANO5/ TMEM16E gene, the cellular and molecular mechanisms behind the pathogenesis of GDD remain unclear. Here, we generated the first knock-in mouse model for GDD with the expression of human mutation p.Cys360Tyr in ANO5. Homozygous Ano5 knock-in mice (Ano5 KI/K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 49 publications
(70 reference statements)
2
8
0
Order By: Relevance
“…Additionally, calcium homeostasis we detected was also impaired significantly in Ano5 −/− osteoclasts (Figure S6). Theses above findings were consistent with the results reported by Li, Wang, Chen, et al (2022) and Li, Wang, Wang, et al (2022). Additionally, we previously reported that osteogenic ability was enhanced significantly in our Ano5 −/− mice, which showed that the expression of ALP and bone formation‐related factors were significantly increased (Wang et al, 2019).…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Additionally, calcium homeostasis we detected was also impaired significantly in Ano5 −/− osteoclasts (Figure S6). Theses above findings were consistent with the results reported by Li, Wang, Chen, et al (2022) and Li, Wang, Wang, et al (2022). Additionally, we previously reported that osteogenic ability was enhanced significantly in our Ano5 −/− mice, which showed that the expression of ALP and bone formation‐related factors were significantly increased (Wang et al, 2019).…”
Section: Discussionsupporting
confidence: 94%
“…Additionally, we previously reported that osteogenic ability was enhanced significantly in our Ano5 −/− mice, which showed that the expression of ALP and bone formation‐related factors were significantly increased (Wang et al, 2019). However, the knockout mice used in Li's study exhibited a decreased mandibular and trabecular bone volume due to reductions in the osteoblast number, maturation, and bone‐forming activity, and Li et al speculated that the phenotype of reduced osteogenic ability was due to diminished [Ca 2+ ] i oscillations (Li, Wang, Chen, et al, 2022; Li, Wang, Wang, et al, 2022). We also found that our Ano5 −/− mice showed an abnormal distribution of trabecular bone, including decreases in the trabecular thickness and number and sparser trabecular bone, whereas the concentration of intracellular calcium in the Ano5 −/− osteoblasts was not altered (data not shown).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is no overlap between mutant loci for bone and muscle diseases; mutations that cause bone lesions do not cause muscle lesions in patients, and vice versa (Marconi et al, 2013). The pathogenic mechanism of ANO5 site‐specific mutations has not yet been clearly explained, and some gene‐edited animal disease models have successfully replicated GDD syndrome‐like manifestations, including long bone bowing, thickened bone cortex, jaw masses, and increased bone fragility (Li et al, 2021; Wang et al, 2019). However, in mouse models, microscopic analysis revealed increased bone mineralization in the jaw lesions but not the microscopic features of fibrous‐osseous lesions generally detected in patients with GDD.…”
Section: Discussionmentioning
confidence: 99%
“…Li et al ( 2022 ) by generating the first knock‐in mouse model for GDD, showed that Ano5 knock‐in mice ( Ano5 KI/KI ) replicated GDD‐like skeletal features. However, Xu et al ( 2015 ) by generating the first Ano5 ‐knock‐out mice showed that genetic ablation that does not cause over pathology in its skeletal and cardiac muscles.…”
Section: Discussionmentioning
confidence: 99%